DLRmagazine 165 – All-rounder in the starting blocks - Birschmann, Nils; Heil, Julia (2020)
Flexible use, easy transportation and clean combustion: hydrogen’s advantages as an energy carrier make it a promising candidate to drive the energy and mobility transition. It provides the basis for alternative fuels, as well as storage for surplus wind and solar energy. DLR researchers are working on making hydrogen’s potential accessible in a wide range of areas. The 'Digital Atlas', which can be used to produce complex maps, has potential as well. These can be used, among other things, to plan energy supply and the security of cities and infrastructures. Just in time for summer we look to DLR Jülich, where the solar tower has gained a strong partner in the form of the new multifocus tower. This means scientists have new opportunities to conduct research with highly concentrated solar radiation. To ensure that no one gets sunburned during summer outdoor activities, DLR's spin-off ajuma developed the UV-bodyguard. This device issues a timely warning of excessive radiation. And those who think that temperatures are too high nonetheless, can delve into the article about the tenth anniversary of DLR’s antenna in Inuvik.